2013
DOI: 10.1111/and.12125
|View full text |Cite
|
Sign up to set email alerts
|

Literature on the aetiology of hypospadias in the last 5 years: molecular mechanism and environmental factors

Abstract: Year-by-year, there has been an increasing number of literature on hypospadias, and most of them are mainly focused on two aspects, namely surgical techniques and aetiology, including the molecular mechanism and associated environmental factors. Surgical techniques and nursing levels are being continuously improved. However, in stark contrast, the study of aetiology still lags behind. Up to now, there is still no consensus on the aetiology of hypospadias, including the molecular mechanism and associated enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, the exact etiology and molecular mechanisms involved in its development are still unclear. 11 Ongoing research sheds light on the genetic, environmental, endocrine, and other factors involved in this defect. 12 Defects in the adrenal gland steroid synthesis pathway can lead to the development of HS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact etiology and molecular mechanisms involved in its development are still unclear. 11 Ongoing research sheds light on the genetic, environmental, endocrine, and other factors involved in this defect. 12 Defects in the adrenal gland steroid synthesis pathway can lead to the development of HS.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Environmental factors are variable as chemical substances, antiandrogen drugs, dietary habits of pregnant mothers, and the medications used in in vitro fertilization and epilepsy treatment. 10,11,[15][16][17][18] Placental insufficiency is one of the reasons that has been mentioned lately. 2 It has been claimed that early placental insufficiency leads to low human chorionic gonadotropin (hCG) secretion, which leads to decreased fetal testosterone production, potentially causing hypospadias at the end of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, our findings showed that the proportions of patients with congenital hypospadias in premature, low birth weight infants and gestational abnormality were significantly higher than those in the control group. To our knowledge, genetic factors have been reported to be highly involved in the etiology of hypospadias in some studies, including gene mutation that contributes to hypospadias in the presence of some genes being important for the development of the urogenital system [ 18 ]. Interestingly, a variety of environmental factors and risk of hypospadias were explored according to Zanden et al; pregnancy complications, maternal drug use, low birth weight, and other environmental factors were regarded as key reasons for increasing the risk of hypospadias [ 3 ].…”
Section: Discussionmentioning
confidence: 99%